History of the Church in eastern Canada and Newfoundland [electronic resource] - Langtry, J. (John), 1834-1906; Society for Promoting Christian Knowledge. (London : Society for Promoting Christian Knowledge; New York : Society's Agents, 1892)
Original issued in series: Colonial church histories. "With map." "Published under the direction of the Tract Committee." Electronic reproduction. Mode of access: Internet. 44